Equipment Investment and the Relative Demand for Skilled Labor: International Evidence - Karnit Flug; Zvi Hercowitz (Inter-American Development Bank, Office of the Chief Economist, 1996)
This paper estimates the effects of equipment investment on relative wages and employment of skilled labor and explores their dynamics. The basic hypothesis is that they are positive, due to either equipment-skill complementarity or to skill advantage in technology adoption. Using a panel data set with a wide rage of countries, the relative wage and relative employment of skilled workers are regressed on lagged investment in machinery and other relevant variables. The results indicate a strong, positive effect of machinery investment on the relative demand for skilled labor.
Keywords: 330